159. efficacy of CD377, a Novel Antiviral Fc-conjugate, Against Seasonal Influenza in Lethal Mouse Infection Models. (31st December 2020) - Levin, James; Amundson, Karin; Shathia, Kim; Borchardt, Allen; Lam, Thanh; Brady, Tom; Noncovich, Alain; Tari, Les
Abstract: Background: Cidara's AVCs (antiviral Fc-conjugates) are novel conjugates of potent, antiviral agents with the Fc domain of human IgG1. CD377 is an AVC development candidate for prevention and treatment of influenza that has broad anti-neuraminidase activity in both enzymatic and cell-based assays and the potential to engage the immune system, as well as a long half-life. Methods: Efficacy studies were conducted in BALB/c mice lethally challenged intranasally at 3x the LD95 with influenza A (H1N1, H3N2) and influenza B (both lineages). CD377 was administered as a single dose subcutaneously (SC) 2 hours after viral challenge. Body weights (BW) and health scores were monitored daily, with 20% BW loss recorded as a mortality. Results: In mice challenged with a lethal dose of an H1N1 strain (A/California/12/2012), a single 0.3 mg/kg dose of CD377 administered 2 hours post-challenge was fully protective (P=0.0015 relative to vehicle) (Fig 1A). In a similar study against a mouse-adapted H3N2 subtype (A/Hong Kong/1/1968), a single dose of CD377 at 0.1 mg/kg was fully protective (P=0.0025) (Fig 1B). In both studies, only a transient loss of BW was observed before mice began recovering weight. The activity of CD377 was also evaluated against both lineages of influenza B (Fig 1C, 1D). Against influenza B/Colorado/06/2017 (Victoria), a single CD377 dose of 0.3 mg/kg was fully protective (P=0.0035) while the Fc-only control dosed at 1 mg/kg was not, as expected. Against the Yamagata lineage (B/Florida/4/2006), CD377 demonstrated full protection at a dose of only 0.03 mg/kg (P=0.0023). Conclusion: A single dose of CD377 (0.3 mg/kg or less) was protective against lethal challenge with several seasonal influenza A/B subtypes. The exceptional PK profile of CD377 combined with potent broad-spectrum activity highlight its potential for use as a long-term preventative against seasonal influenza. Seasonal influenza efficacy Disclosures: James Levin, PhD, Cidara Therapeutics (Shareholder) Karin Amundson, BSc, Cidara Therapeutics (Shareholder) Allen Borchardt, PhD, Cidara Therapeutics (Employee) Thanh Lam, PhD, Cidara Therapeutics (Shareholder) Tom Brady, PhD, Cidara Therapeutics (Shareholder) Alain Noncovich, PhD, Cidara Therapeutics (Shareholder) Les Tari, PhD, Cidara Therapeutics (Shareholder)